(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Healthcare system plays an important and crucial role in providing the various healthcare services to people living in different geographical area. it is also helps to improve, restore and refuel the energy in the body which helps to maintain and increasing the productivity and efficiency of the people. In this investigation, researchers have mainly paid their focus on the role and problems of 100bedded hospitals in Solapur district. This research investigation has also tried to explore the various factors determine the use of 100 bedded hospitals in selected investigation area. Researchers have used exploratory and descriptive research method. This research investigation was purely based on primary data which was collected through theself-structured questionnaire, personal interview and observation.This research investigation were found various problems in 100 bedded hospitals such as congested improper treatment and diagnosing of diseases, space in patient room, inadequate size of waiting room,absence of well-equipped ambulance and Absence of proper communication in medical staff and patients in selected 100 bedded hospitals in selected investigation area during the study period.Researchers have concluded that 100 bedded hospitals play significant role in providing various healthcare services and facilities under the one roof at reasonable price in selected investigation area.